MiR‐429 suppresses proliferation and invasion of breast cancer via inhibiting the Wnt/β‐catenin signaling pathway - Zhang, Liping (Thorac Cancer, 2020)
BACKGROUND: microRNAs (miRNAs) have been verified as molecular targets for regulating tumor proliferation, invasion, and metastasis in tumor progression. However, the relationship between miRNAs and cellular energy metabolism in breast cancer still needs to be clarified. This study aimed to investigate the role of miR‐429 in breast cancer progression. METHODS: Bioinformatic analyses were employed to detect the relationship between miR‐429 and cancer‐related signaling pathways. We used a Kaplan‐Meier curve to analyze survival rate in patients with high or low expression of miR‐429. We used real‐time quantitative PCR (RT‐qPCR) to detect the expression of miR‐429 in different cell lines. Sh‐con, over‐miR‐429, miR‐429 inhibitor, and sh‐inhibitor control were transfected. Colony formation and EDU assay were used to detect the proliferation of transfected cells. Wound healing and transwell assays were performed to detect the mobility and invasion ability of transfected cells. Western blot assay was used to detect relative protein expression in transfected cells and different tissues. Bioinformatic analyses were conducted to detect the target proteins expression in different breast cancer databases. Dual luciferase reporter assay was used to confirm the binding site between miR‐429 and fibronectin 1 (FN1). RESULTS: The results of our study indicate that MiR‐429 and its target genes are associated with cancer‐related signaling pathways and that higher miR‐429 expression corresponds with a better prognosis. When miR‐429 was overexpressed, the proliferation, invasion of MDA‐MB‐231 were inhibited. MiR‐429 was able to suppress the Wnt/β‐catenin signaling pathway, and FN1 overexpression could rescue the influence of over‐miR‐429. CONCLUSIONS: The results of our study suggest that miR‐429 suppresses the proliferation and invasion of breast cancer via inhibiting the Wnt/β‐catenin signaling pathway.